Assessment of pathogenesis of infective endocarditis by plasma IgG antibody titer test against periodontal bacteria. Issue 10 (17th August 2017) - Isoshima, Daichi; Yamashiro, Keisuke; Matsunaga, Kazuyuki; Shinobe, Michitaka; Nakanishi, Nagako; Nakanishi, Izumi; Omori, Kazuhiro; Yamamoto, Tadashi; Takashiba, Shogo
Key Clinical Message: Oral bacteria cause infective endocarditis (IE), so severe periodontitis is thought to be high risk for IE. We suggest the identification of high‐risk patients by an IgG antibody titer test against periodontal bacteria might become common screening test. Abstract : Oral bacteria cause infective endocarditis (IE), so severe periodontitis is thought to be high risk for IE. We suggest the identification of high‐risk patients by an IgG antibody titer test against periodontal bacteria might become common screening test.